زيارة المسلم معابد الكفار في ماليزيا من منظور الفقه الإسلامي والسياسة الشرعية MUSLIMS VISITING NON-MUSLIM TEMPLES IN MALAYSIA FROM THE PERSPECTIVE OF ISLAMIC JURISPRUDENCE AND SHARI'AH POLICY (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
Malaysia is made up of different religions, Islam, Christianity, Hinduism, Buddhism and others. For this reason, there are many temples in this country, both in cities and villages. In March 2023, a controversy arose over a programme called ‘Let's Visit the Church’. As a result, a few individuals and organisations have banned Muslims from participating in it, while at the same time there are those who allow it. This leads to questions among the community, ‘What is the opinion of Sharia on the ruling of Muslims visiting the temples of infidels?’ This research aims to discuss the different jurists on the ruling of entering the temples of infidels, and then weighing these opinions according to the strength of the evidence and arguments. In addition, this research will be from the point of view of Shari'ah policy, the position that the Malaysian government should take between allowing or forbidding Muslims to visit infidel temples. This research follows a qualitative study approach. To gather information, the researcher uses the inductive method by tracing the opinions of jurists from the four schools of thought in many traditional and Hadith books. He also uses the analytical method in explaining and discussing each of these opinions in detail, and then the deductive method in weighting the opinions of the jurists on the ruling of the visit in terms of the science of jurisprudence and issuing suggestions to the Malaysian government based on the science of Shari'ah policy. One of the findings of the research is that the scholars differed on the ruling of entering the temples of infidels into three opinions: permissible, unacceptable and prohibited. The researcher favours the permissible view over the other two due to the strength and clarity of its evidence and is supported by many of the traditions of the companions and followers. However, from the perspective of Sharia policy, the researcher suggests to the Malaysian government to prohibit Muslim citizens in this country from visiting the temples of infidels without any need, and this prohibition is in accordance with the prevention of harm, the purposes of preserving religion, custom, and the jurisprudential rule; preventing harms is prior to bringing benefits.